Anti-Ulcerogenic Potential of Ficus bengalensis Leaf, Biochemical Parameter & Histopathological Study - Mayank Kulshreshtha, Mradul Goswami, Chandana V. Rao, Vrish D Ashwlayan, Sachdev Yadav (Journal of Applied Pharmaceutical Science)
The effect of aqueous extract of Ficus bengalensis (FBE) was assessed in different acute and chronic gastric ulcer models in rats. Gastric ulcers induced in swiss albino rats (200g, N=6) by oral administration of aspirin suspension and pylorus ligation. The anti ulcer activity was assessed by determining and comparing the ulcer index in the test drug groups with that of the vehicle control and standard ranitidine & sucralfate. FBE, 250–500 mg/kg administered orally, twice daily for 5 days showed dose-dependent ulcer protective effect in pylorus ligation (51.28, 63.24% protection, P < 0.01 to P < 0.001), aspirin (28.94, 64.91 protection, P < 0.001). The parameters taken to assess antiulcer activity were pH of gastric juice, total acidity and ulcer index. The results indicated that aqueous extract significantly (p
Keywords: Ficus bengalensis, Pylorus ligation, Acidity, Ulcer index.